1978
DOI: 10.1016/s0140-6736(78)90305-7
|View full text |Cite
|
Sign up to set email alerts
|

Altered Theophylline Pharmacokinetics During Acute Respiratory Viral Illness

Abstract: The plasma half-life of theophylline was determined during and 1 month after serologically confirmed upper-respiratory-tract viral illness in six children with chronic asthma. In this group the plasma-theophylline half-life (mean = 419.8 min) was significantly longer during the acute stage of their illness than 1 month later (mean 249.9 min). There was no appreciable change in half-life in 4 patients who were febrile but in whom seroconversion did not occur. These preliminary results suggest that certain upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
4

Year Published

1982
1982
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(78 citation statements)
references
References 2 publications
3
71
0
4
Order By: Relevance
“…In one study, the plasma half-life of theophylline was determined during and 1 month after serologically confirmed upper-respiratory-tract viral illness in six children with chronic asthma. In this group the plasma theophylline half-life (mean = 419.8 minutes) was significantly longer during the acute stage of illness than 1 month later (mean = 249.9 minutes) (Chang et al, 1978). Serum theophylline levels also increase, often to toxic levels, following influenza vaccination (Renton et al, 1980).…”
Section: Evidence For Potential Phenoconversion Of Dmes In Other Inflmentioning
confidence: 89%
“…In one study, the plasma half-life of theophylline was determined during and 1 month after serologically confirmed upper-respiratory-tract viral illness in six children with chronic asthma. In this group the plasma theophylline half-life (mean = 419.8 minutes) was significantly longer during the acute stage of illness than 1 month later (mean = 249.9 minutes) (Chang et al, 1978). Serum theophylline levels also increase, often to toxic levels, following influenza vaccination (Renton et al, 1980).…”
Section: Evidence For Potential Phenoconversion Of Dmes In Other Inflmentioning
confidence: 89%
“…Changes in P450-mediated drug clearance, associated with inflammation, have been demonstrated in humans with various infections including influenza and HIV (Chang et al, 1978;Jones et al, 2010), as well as in patients with cancer and heart failure (Frye et al, 2002;Rivory et al, 2002). In both humans and laboratory animals, most P450 enzymes studied are down-regulated (Aitken et al, 2006), primarily by pretranslational mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The first documented observation reported that an upper respiratory viral infection in asthmatic children increased theophylline plasma concentrations and half-life (Chang et al, 1978). Actually, numerous reports have documented that influenza infections reduce the rate of biotransformation of theophylline and other drugs (Cheng and Morgan, 2001;Renton, 2001).…”
Section: Introductionmentioning
confidence: 99%